Frequency and location of head impact exposures in individual collegiate football players - Crisco, J. J.; Fiore, R.; Beckwith, J. G.; Chu, J. J.; Brolinson, P. G.; Duma, S.; McAllister, T. W.; Duhaime, A.-C.; Greenwald, R. M. (Journal of Athletic Training, 2010)
Context: Measuring head impact exposure is a critical step toward understanding the mechanism and prevention of sport-related mild traumatic brain (concussion) injury, as well as the possible effects of repeated subconcussive impacts.